Violence against Women in Eka Kurniawan’s Vengeance Is Mine, All Others Pay Cash - Dian Febriyanti; Pratiwi Retnaningdyah (Tell : Teaching of English Language and Literature Journal, 2021)
The aim of this article is to analyze the types of violence against women depicted in Eka Kurniawan’s Vengeance Is Mine, All Others Pay Cash also to reveal the process of several female characters from being disempowered (after received violence by men) to empowering themselves. Those are global and common issues that society would face every day. This study uses thematic analysis on the basis of Gender-based Violence (GBV) to categorize the type of violence based on a theory of feminist by Beauvoir and also using Naila Kabeer’s perspective to reveal that violence affect women in empower and disempower ways. The female characters that receive violence are Scarlet Blush, Iteung, Young Widow, and Jelita. The types of violence that occurred are sexual violence, physical violence, verbal violence, and psychological violence. However, the result of women’s empowerment only causes Iteung itself, she is the only one who can survive and be empowered after fighting against patriarchal culture, while Scarlet Blush is the opposite.